Implementation of Blockchain in Achieving Transparency and Security in Management Systems - Oldi Malfri Lambonan; Al’fazri Rahmat Akapu; Ariefano Sinatra Rawung; Muflihah Azizah Mampa; Tiara Erika Rompah (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The rapid growth of digital technologies has encouraged organizations to adopt management systems that prioritize transparency, security, and efficiency. Blockchain has emerged as a transformative innovation capable of reshaping conventional management processes through its decentralized and tamper-resistant architecture. This study analyzes the implementation of blockchain in enhancing transparency and security within management systems. A literature review approach was used to examine recent scholarly publications related to blockchain applications across various organizational settings. The findings indicate that blockchain significantly improves data integrity, prevents fraud, and strengthens accountability through distributed ledgers, cryptographic mechanisms, and smart contracts. However, challenges such as scalability limitations, infrastructure readiness, regulatory uncertainties, and limited technical literacy remain major obstacles. This study concludes that blockchain presents substantial benefits, but its effective implementation requires a comprehensive and strategic approach to ensure organizational readiness and long-term sustainability.